Khảo sát khả năng ức chế ăn mòn thép CT3 của một số hỗn hợp ức chế thân thiện với môi trường trong màng sơn hữu cơ - Liêm, Đào Quang; Tam, Nguyễn Văn; Tuấn, Bùi Quang; Hoan, Lai Thị; Lâm, Phạm Tiến; Sơn, Khuất Quang (Vietnam Journal of Chemistry, 2012)
Organic coatings can not completely separate metal substrates from aggressive medium, so the present of inhibitors in organic coatings plays an important role for inhibitive ability of these coatings. Some traditional inhibitors, such as ZnCrO4, PbO2..., have been used for along time, but these inhibitors are toxic. Therefore, finding new environmental-friendly inhibitors has been attracted many researches. In this work, we would like to present some result about properties of calcium phosphate molypdate (CPM), mixture of zinc molypdate and calcium phosphate (ZMCP) in epoxy coating on CT3 steel. Inhibitive properties of these inhibitive systems are investigated by electrochemical methods: monitoring open circuit potential and electrochemical impedance spectroscopy, electrochemical polarization curves. Influence of these mixtures on mechanical properties of this coating system is also investigated. The results show that these inhibitive systems have good anticorrosive ability and they do not change the mechanic properties of epoxy and alkyd coatings.